Tantangan Dan Arah Dakwah Di Tengah Ancaman Pandemi Covid-19 - Jauhari Hasan (Ar-Raniry State Islamic University, Indonesia, 2020)
Da'wah is a duty of Islamic syar'i that given to every Muslim according to their abilities. In the running of da'wah, it is always faced with various challenges in every space and time. Currently, da’wah is being faced with a global and an invisible challenges, namely covid-19. This virus had choked up the dakwah movement, the interaction between the da'i and mad'u was hindered by the procedure of social distance. Therefore, the direction of da’wah in the era of Covid-19 needs to be formulated. To find the ideal direction of da'wah, the research has been done at the “Forum Dakwah Perbatasan (FDP)”that located in the capital city of Aceh Province. This forum is ane of the Islamic organizations that are committed to carrying out da'wah even in the midst of a covid storm. The data that related to the challenges and direction of da'wah were obtained through in-depth interviews, documentation in the office of FDP and observations in the FDP da'wah area, especially in Danau Paris District, Aceh Singkil and in Lhokseumawe City. Based on the understanding and analysis of the data, the direction of da’wah carried out by this organization emphasizes the development of education, economic strengthening and humanitarian assistance, and health campaigns. So, the activities of da'wah is still running well while maintaining of health protocols. Dakwah merupakan sebuah kewajiban syar’i yang dipundakkan kepada setiap muslim sesuai kemampuan yang ada pada dirinya. Dalam menjalankan dakwah selalu dihadapkan dengan berbagai tantangan yang beraneka ragam sesuai dengan perkembangan ruang dan waktu. Saat ini dakwah sedang dihadapkan dengan tantangan yang bersifat global dan tidak tampak oleh mata, yaitu covid-19. Wabah ini telah membuat pergerakan dakwah menjadi tersendat, interaksi antara da’i dengan mad’u menjadi terhalang dengan anjuran menjaga jarak. Karena itu arah dakwah di tengah ancaman covid-19 ini perlu dirumuskan. Untuk menemukan arah dakwah yang ideal, maka dilakukan riset terhadap organisasi Islam yang komit menjalankan dakwah meskipun di tengah badai covid, yaitu Forum Dakwah Perbatasan (FDP) yang berkedudukan di Ibu Kota Provinsi Aceh. Data terkait tantangan dan arah dakwah ini diperoleh melalui indepth interview dengan beberapa pengurus FDP, dari beberapa dokumen yang terimpan di sekretariat FDPdi Banda Aceh dan ditambah dengan pengalaman observasi di wilayah dakwah FDP khususnya di Kecamatan Danau Paris, Kabupaten Aceh Singkil dan di Kota Lhokseumawe. Berpijak dari pemahaman dan analisis terhadap data yang terkumpulkan, maka arah dakwah yang dilakukan oleh organisasi ini lebih menekankan pada pengembangan Pendidikan, Penguatan ekonomi dan bantuan Kemanusiaan, serta kampanye kesehatan. Aktivitas dakwah tersebut berjalan dengan baik meskipun tetap memperhatikan protokol kesehatan